Теория электропривода: лабораторный практикум - Однокопылов И. Г. Иван Георгиевич; Дементьев Ю. Н. Юрий Николаевич; Семенов С. М. Сергей Михайлович; Краснов И. Ю. Иван Юрьевич (Томск, Изд-во ТПУ, 2012)
Заглавие с титульного экрана